2015
DOI: 10.25035/ijare.09.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Toward Defining Water Competency: An American Red Cross Definition

Abstract: Water competency entails more than a perception of just being able to swim and an operational definition of water competency is necessary for learn-to-swim program evaluation and policy development. To devise an operational definition, members of the American Red Cross Scientific Advisory Aquatic subcouncil surveyed nine key national (United States) organizations, 14 international organizations, and 19 other key informants involved with water safety and swimming activities for their requirements for swimming i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…This issue of the International Journal of Aquatic Research and Education features a study conducted by members of the American Red Cross's Scientific Advisory Council's aquatic subcouncil (see Quan, et al 2015 in this issue). Their stated goal of the study and paper is to identify current ways that aquatic professionals test proficiency in swimming (i.e., water competency) and based on that information to construct an operational definition for water competency that might eventually be recognized worldwide in an effort to understand how being competent in the water serves as a deterrent to drowning.…”
Section: Impact Of Aquatic Readiness and Water Competence On Learn-tomentioning
confidence: 99%
See 2 more Smart Citations
“…This issue of the International Journal of Aquatic Research and Education features a study conducted by members of the American Red Cross's Scientific Advisory Council's aquatic subcouncil (see Quan, et al 2015 in this issue). Their stated goal of the study and paper is to identify current ways that aquatic professionals test proficiency in swimming (i.e., water competency) and based on that information to construct an operational definition for water competency that might eventually be recognized worldwide in an effort to understand how being competent in the water serves as a deterrent to drowning.…”
Section: Impact Of Aquatic Readiness and Water Competence On Learn-tomentioning
confidence: 99%
“…In the Quan et al (2015) paper, the authors identified what they believed are the key elements or items in defining a person's degree of water competency. They include several specific tasks that could be associated with the basic skill strands mentioned in the previous paragraph that already comprise the American Red Cross L-T-S levels.…”
Section: Primary Elements Of Water Competencementioning
confidence: 99%
See 1 more Smart Citation
“…An international position statement recommended completing a minimum distance of 25 m in addition to a range of other water safety skills including water entry/exit, floating, and rescue skills (International Life Saving Federation, 2012). A review of 14 international organizations found variable distance requirements within their tests of water safety with 25 m being the most frequently reported distance although the authors noted that the skills and competencies will be environment-and task-specific (Quan, Ramos, Harvey, Kublick, Langendorfer, Lees, et al, 2015). A recent study in Bangladesh used a 25 m distance as a measure of 'naturally acquired swimming ability,' the assessment being conducted in open water deeper than the candidates' own height and included being able to exit the water (Rahman, Linnan, Mashreky, Hossain, & Rahman, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Re-establishing a historic culture of swimming among African Americans ought to start with assessing and developing water competencies among the most vulnerable persons including especially African American children (Pharr, Irwin, Layne, & Irwin, 2018). The American Red Cross has identified water competency as the skill to (1) enter the water with full submersion; (2) recover to the surface and float or tread for at least 1 minute; (3) turn 360 degrees and orient toward an exit point; (4) level off and move on font and/or back position for at least 25 yards; and (5) exit safely from the water (Quan et al, 2015). More recently, Stallman, Moran, Quan, and Langendorfer (2017) expanded the definition of water competency and proposed 15 psychomotor tasks, cognitive knowledges, and affective attitudes and judgments.…”
Section: Call To Actionmentioning
confidence: 99%